2022
DOI: 10.1080/21655979.2022.2047406
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of NOD-like receptor protein 3 inflammasome activation and macrophage M1 polarization by hederagenin contributes to attenuation of sepsis-induced acute lung injury in rats

Abstract: Acute lung injury (ALI) is a major leading cause of death in sepsis patients. Hederagenin (HG), derived from Hedera helix Linné , has anti-inflammatory effects, while its role in sepsis-induced ALI has not been elucidated. In vivo , rats were subjected to cecal ligation and puncture to induce ALI and then treated with HG (12.5, 25, or 50 mg/kg) by gavage. Administration of HG raised survival rate, ameliorated lung injury, and decreased lung wet/dry ratio and inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Previous reports have identified the anti‐inflammatory activity of hederagenin (Kim et al, 2017; Lee et al, 2015), while the relationship between hederagenin and NLRP3 inflammasome is largely unknown in diabetic nephropathy. In this study, we found that hederagenin mitigated NLRP3 inflammasome activation in HRMCs and HRPTEpiCs under HG conditions, which was also consistent to that in sepsis‐induced acute lung injury (Wang & Zhao, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…Previous reports have identified the anti‐inflammatory activity of hederagenin (Kim et al, 2017; Lee et al, 2015), while the relationship between hederagenin and NLRP3 inflammasome is largely unknown in diabetic nephropathy. In this study, we found that hederagenin mitigated NLRP3 inflammasome activation in HRMCs and HRPTEpiCs under HG conditions, which was also consistent to that in sepsis‐induced acute lung injury (Wang & Zhao, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…However, the molecular mechanism of sepsis complicated by ALI remains unclear. Wang et al showed that hederagenin inhibition by inhibiting the NF- κ B pathway and NLRP3 inflammasome activation reduces inflammatory response and macrophage M1 polarization, thereby playing a protective role against sepsis-induced ALI [ 6 ]. Jiao et al found that exosomal miR-30d-5p from polymorphonuclear neutrophils contributed to sepsis-related ALI by inducing M1 macrophage polarization and priming macrophage pyroptosis through activating NF- κ B signaling [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Hederagenin is a kind of pentacyclic triterpenoid compound with natural biological activity, which can be extracted and separated from a variety of medicinal plants. It has many pharmacological effects, such as anti-oxidation, enhancing immunity, promoting apoptosis and anti-fibrosis, [15,16] while it can also protect blood vessels from atherosclerosis by improving lipid metabolism and inhibiting lipid deposition. [17] In addition, hederagenin can also inhibit the expression of nitric oxide synthase, cyclooxygenase-2, and nuclear factor κB (NF-κB) induced by lipopolysaccharide stimulation, thus alleviating the inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%